DEVELOPMENT OF INSTRUMENT FOR HIGH SCHOOL STUDENTS' READING LITERACY AND NUMERATION ON THERMOCHEMICAL MATERIAL - Siswaningsih, Wiwi; Rahmawati, Triannisa; Salsabila, Audria; Zahira, Alfina Dzabillah; Nahadi, Nahadi; Suhanda, Hokcu; Mora, Abraham; Lee, Won Koo (Lantanida Journal, 2024)
The aim of this research is to produce a minimum competency assessment instrument (MCA) on thermochemical material that meets the test criteria that is suitable for measuring students' reading literacy and numeracy in terms of validity, reliability, level of difficulty and distinguishing power. The research design used is a development and validation design. The participants involved in this research were high school students at one of the high schools in Bandung City as respondents and validators consisting of 3 lecturers and 2 teachers in their fields. The product resulting from this research is the MCA test instrument on thermochemical material which consists of 5 reading literacy questions and 15 numeracy questions. This test instrument was declared valid based on content validity and based on empirical validity, 16 questions were valid and 4 questions were invalid. The reliability test results showed that the reliability value for the objective questions was 0.73, while the reliability value for the description questions was 0.77 and both were declared reliable. The results of the MCA instrument competency level analysis show that students' reading literacy and numeracy competencies are included in the basic category and require special intervention with a refractive index of 1.53 and 1.00.